Psychopathic Personality Traits and the Successful Criminal - Boccio, Cashen M. (International journal of offender therapy and comparative criminology, 2018)
A significant body of literature links psychopathy and psychopathic personality traits with criminal behavior and involvement with the criminal justice system. However, very little research has examined whether psychopathic personality traits are related to being a successful criminal (e.g., evading detection). This study addresses this gap in the literature by examining whether psychopathic personality traits are associated with the likelihood of being processed by the criminal justice system (i.e., arrest). Our findings reveal that psychopathic personality traits are generally not associated with criminal success. Specifically, individuals with high levels of psychopathic personality traits commit more crimes and report more arrests, but they do not seem to have an advantage when it comes to avoiding arrest for the crimes they commit. We discuss the implications of these findings for the psychopathy literature.